Estudo das variáveis de processo na produção e na purificação do biodiesel de soja via rota etílica - Lopes, Adriana Carla de Oliveira (2008)
Biodiesel is an alternative fuel, renewable, biodegradable and no toxic. The transterification of vegetable oils or animal fat with alcohol is the most usual manner of production of that fuel. The objectives of this study were to evaluate the process of production of biodiesel in pilot scale, and carry out the study of the variables that influence the process of etanolise of soybean oil, using a catalyst basic sodium hydroxide, in order to obtain the conditions operational leading to greater conversion to biodiesel and also assess the variables that influence the process of purification of fuel. The pilot plant consists of a glass reactor with a capacity of 3 L, provided with: Jersey movement of heated water and mechanical agitation. The experiments to study the production of biodiesel from soybeans have been conducted in accordance with the planning factor fragmented. Already the study of the same purification process was conducted in accordance with a schedule full factorial. The variables studied for the production process were: temperature of reaction (30-70 oC); concentration of catalyst (0,5-1,5%), time of reaction (0,5-2 hours); speed of agitation ( 150-350 rpm), and ethanol molar ratio: soybean oil (4:1-10:1). And these variables for the purification process were: temperature (30-70 ° C) and pH (2-5) of water washing. In the study of the production of biodiesel from soybean parameter of the evaluation was to conversion into biodiesel, determined by gas chromatography, using the chromatograph VARIAN, model CP-3800, and for studying the process of purification, the parameter of response was the amount of Water spent to counteract the biodiesel from soybean. At the end of the work was verified that the variables: molar ratio oil / alcohol, the reaction temperature and concentration of the catalyst has strong influence in the production of biodiesel. And as the temperature and pH of the water for washing exercise strong influence in the soybean biodiesel purification process.